2002
DOI: 10.4049/jimmunol.168.3.1490
|View full text |Cite
|
Sign up to set email alerts
|

Selective Decrease in Circulating Vα24+Vβ11+ NKT Cells During HIV Type 1 Infection

Abstract: CD1d-restricted NKT cells express an invariant TCR and have been demonstrated to play an important regulatory role in a variety of immune responses. Invariant NKT cells down-regulate autoimmune responses by production of type 2 cytokines and can initiate antitumor and antimicrobial immune responses by production of type 1 cytokines. Although defects in the (invariant) Vα24+Vβ11+ NKT cell population have been observed in patients with cancer and autoimmune diseases, little is known regarding the protective role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
112
2
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(129 citation statements)
references
References 47 publications
14
112
2
1
Order By: Relevance
“…Loss or dysfunction of these cells occurs in autoimmune conditions (6)(7)(8)10), cancer (9,11), and viral infections (16)(17)(18)42). Investigation of the pathways and sites for development and differentiation of human V␣24 NK T cells is, therefore, important both for the basic understanding of the biology of these cells and for potential therapeutic interventions to restore or improve V␣24 NK T cell function in certain diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss or dysfunction of these cells occurs in autoimmune conditions (6)(7)(8)10), cancer (9,11), and viral infections (16)(17)(18)42). Investigation of the pathways and sites for development and differentiation of human V␣24 NK T cells is, therefore, important both for the basic understanding of the biology of these cells and for potential therapeutic interventions to restore or improve V␣24 NK T cell function in certain diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The primary role of CD1d-restricted NK T cells is thought to be the regulation of immune responses, and several reports (6-11) support a role for NK T cell dysfunction in the pathogenesis of autoimmune diseases and cancers, as well as in murine models of autoimmunity (12)(13)(14)(15). They are lost in HIV-1 infection in humans (16)(17)(18) and lymphocytic choriomeningitis virus infection in mice (19), and they can be activated to participate in defense against hepatitis B virus and cytomegalovirus in mice (20,21).…”
Section: H Uman Natural Killer (Nk) T Cells Are Innate Immune Cellsmentioning
confidence: 99%
“…The role for NKT cells in the pathogenesis of infectious diseases is less clear. However, the CD4 + V § 24 NKT cells were recently found to be extremely sensitive to HIV infection [11,23,24], and the corresponding murine V § 14 NKT cells are lost during acute infection with lymphocytic choriomeningitis virus (LCMV) [25].…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal analysis revealed that the iNKT-cell depletion occurs largely during the first year after seroconversion [21]. The plasma HIV-1 RNA concentration correlates negatively with the CD4 1 iNKT-cell frequency but not with the total iNKT-cell frequency [20,21].…”
Section: Changes In Human Inkt Cells During Viral Infectionsmentioning
confidence: 99%